Immunological Barriers to Stem Cell Therapy in the Central Nervous System - Gregory E. Tullis; Kathleen Spears; Mark D. Kirk (Stem Cells International)
The central nervous system is vulnerable to many neurodegenerative disorders such as Alzheimer’s disease that result in the extensive loss of neuronal cells. Stem cells have the ability to differentiate into many types of cells, which make them ideal for treating such disorders. Although stem cell therapy has shown some promising results in animal models for many brain disorders it has yet to translate into the clinic. A major hurdle to the translation of stem cell therapy into the clinic is the immune response faced by stem cell transplants. Here, we focus on immunological and related hurdles to stem cell therapies for central nervous system disorders.